The synthesis of (+/-)-heliotridane and (6S,7S)-dihydroxyheliotridane via sequential hydrogen atom abstraction and cyclisation - Robertson, J; Peplow, M; Pillai, J (1996)
Treatment of N-(3-bromo-3-butenyl)pyrrolidine derivatives with tributyltin hydride and AIBN leads to hydrogen atom transfer of the intermediate vinyl radicals to give α-amino radicals which then cyclise stereoselectively yielding pyrrolizidines 1 and 13.